Unattended Pregnancies and Perinatal Mortality in Georgia - Manjavidze T; Rylander C; Skjeldestad FE; Kazakhashvili N; Anda EE (Dove Medical Press, 2020)
Tinatin Manjavidze,1 Charlotta Rylander,1 Finn Egil Skjeldestad,1 Nata Kazakhashvili,2 Erik Eik Anda1 1Department of Community Medicine, Faculty of Health Sciences, University of Tromsø – The Arctic University of Norway, Tromsø 9037, Norway; 2Department of Public Health, Faculty of Medicine, Ivane Javakhishvili Tbilisi State University, Tbilisi 0179, GeorgiaCorrespondence: Tinatin Manjavidze 35a Guramishvili Ave, Tbilisi 0178, GeorgiaTel +995 598292936Email tinatin.manjavidze@uit.noIntroduction: The majority of pregnant women in Georgia attend the free-of-charge, national antenatal care (ANC) programme, but over 5% of pregnancies in the country are unattended. Moreover, Georgia has one of the highest perinatal mortality (PM) rates in Europe (11.7/1000 births).Purpose: To assess the association between unattended pregnancies and the risk of PM.Methods: Data were extracted from the Georgian Birth Registry (GBR) and the national vital registration system. All mothers who had singleton births and delivered in medical facilities in Georgia in 2017– 2018 were included in the study and categorised into attended pregnancies (at least one ANC visit during pregnancy) and unattended pregnancies (no ANC visits during pregnancy). After exclusions, the study sample included 101,663 women and their newborns, of which 1186 were either stillborn or died within 7 days. Logistic regression analysis was used to assess the effect of unattended pregnancies on PM.Results: During the study period, the PM rate was 12.9/1000 births. In total, 5.6% of women had unattended pregnancies. The odds of PM among women with unattended pregnancies were more than double those among women with attended pregnancies (odds ratio=2.21, [95% confidence interval: 1.81– 2.70]). Multiparous women with higher education and who resided/delivered outside of Tbilisi were significantly less likely to experience PM.Conclusion: The risk of PM doubled among women with unattended pregnancies. Six percent of PM cases were attributable to unattended pregnancies. Targeting women with previous unattended pregnancies will likely reduce the PM rate in Georgia.Keywords: stillbirth, early neonatal mortality, antenatal care, birth registry